2016
DOI: 10.1002/mc.22542
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐21 regulates the ERK/NF‐κB signaling pathway to affect the proliferation, migration, and apoptosis of human melanoma A375 cells by targeting SPRY1, PDCD4, and PTEN

Abstract: This study aims to explore the effects of microRNA-21 (miR-21) and ERK/NF-κB signaling pathway on human melanoma A375 cells. The melanoma tissues and adjacent normal tissues were obtained from 45 melanoma patients. qRT-PCR was conducted to quantify the expression of miR-21 and the gene mRNA expressions. Human melanoma A375 cells were divided into the Mock, negative control (NC), miR-21 inhibitors, miR-21 inhibitors + siRNA-SPRY1, miR-21 inhibitors + siRNA-PDCD4, and miR-21 inhibitors + siRNA-PTEN groups. Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
(40 reference statements)
2
46
0
Order By: Relevance
“…HCC is the third factor causing death that related to the cancers in the world, and also the major reason of mortality in patients with cirrhosis . Moreover, it has been unearthed that the abnormal expression of miRNAs was associated with the development as well as tumorigenesis in human cancers . There was a recent research has proved the expression and prospective functional pathways of miR‐124‐3p in HCC, in which the relationship between miR‐124‐3p and HCC has been ascertained, and our study was designed to explore the combined role of MDZ, miR‐124‐3p, and its target gene PIM‐1 in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC is the third factor causing death that related to the cancers in the world, and also the major reason of mortality in patients with cirrhosis . Moreover, it has been unearthed that the abnormal expression of miRNAs was associated with the development as well as tumorigenesis in human cancers . There was a recent research has proved the expression and prospective functional pathways of miR‐124‐3p in HCC, in which the relationship between miR‐124‐3p and HCC has been ascertained, and our study was designed to explore the combined role of MDZ, miR‐124‐3p, and its target gene PIM‐1 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…19 Moreover, it has been unearthed that the abnormal expression of miRNAs was associated with the development as well as tumorigenesis in human cancers. 20 There was a recent research has proved the expression and prospective functional pathways of miR-124-3p in HCC, 21 in which the relationship between miR-124-3p and HCC has been ascertained, and our study was designed to explore the combined role of MDZ, miR-124-3p, and its target gene PIM-1 in HCC. Collectively, we have found that MDZ could mediate miR-124-3p/PIM-1 axis to regulate the molecular mechanisms of malignant phenotype of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of these 2 genes respectively leads to osteoblast proliferation and differentiation. [19][20][21][22][23] In this study, we demonstrated that exosomes produced by GHPA cells can be internalized by osteoblasts, resulting in exosomal miR-21-dependent promotion of osteoblasts proliferation, synthesis of osteocalcin (OCN) and collagen I, and bone formation through a pathway distinct from the traditional GH/IGF-1 axis.…”
Section: Introductionmentioning
confidence: 82%
“…In our study, we also find it is abundant in several different tumour cell lines (Supplementary 3c, 7c). It is well documented that miR-21a is an oncogenic miRNA to regulate cancer cell proliferation, migration and apoptosis by suppressing the expression of tumour suppressors including PTEN (Mao et al, 2017) and PDCD4 (Asangani et al, 2008;Mao et al, 2017). Recently miR-21a emerges to have a role in regulating inflammatory response and to stimulate production of anti-inflammatory cytokine IL-10 in macrophage through miR-21/PDCD4 axis (Das et al, 2014).…”
Section: Discussionmentioning
confidence: 99%